Strengthening Primary Health Care in Low- and Middle-Income Countries: Generating Evidence Through Evaluation. (July 2014) - Rule, John; Ngo, Duc Anh; Oanh, Tran Thi Mai; Asante, Augustine; Doyle, Jennifer; Roberts, Graham; Taylor, Richard
Since the publication of the World Health Report 2008, there has been renewed interest in the potential of primary health care (PHC) to deliver global health policy agendas. The WHO Western Pacific Regional Strategy 2010 states that health systems in low- and middle-income countries (LMICs) can be strengthened using PHC values as core principles. This review article explores the development of an evidence-based approach for assessing the effectiveness of PHC programs and interventions in LMICs. A realist review method was used to investigate whether there is any internationally consistent approach to evaluating PHC. Studies from LMICs using an explicit methodology or framework for measuring PHC effectiveness were collated. Databases of published articles were searched, and a review of gray literature was undertaken to identify relevant reports. The review found no consistent approach for assessing the effectiveness of PHC interventions in LMICs. An innovative approach used in China, which developed a set of core community health facility indicators based on stakeholder input, does show some potential for use in other LMIC contexts.